IMPROVEMENT OF THE GIS-BASED MANAGEMENT SYSTEM OF STATE GEODESIC NETWORKS - Abdurakhmonov Abdukhokim Abduvakhobovich (Western European Studies, 2025)
This in the article state geodetic networks using GIS (Geographic Information System) technologies based on management system improvement issues scientific and practical The main purpose of the study is to analyze the on a scale geodetic points database on a single GIS platform centralized without management, automation and information accuracy from increasing consists of. The article geodetic points information digitize them in real time in mode update and automatic warning systems create according to proposals have been developed. GIS programs — ArcGIS, PostGIS and GeoServer The model developed on the basis of the example of the Fergana region from the test was held. Results to the analysis according to, new system information again work reduced time by 60%, management increased efficiency by 40–50% and points accuracy noticeable at the level improved. In the article also international with experiences ( USA, Germany, Russia, South Korea) comparator analyses brought to Uzbekistan to the conditions customized management model offer Research results geodesy, cartography, land cadastre and engineering GIS technologies in the fields of current to grow for scientific and practical basis creates.
Keywords: GIS; geodesy; network; digitization